Exercise merging physical and cognitive stimulation improves physical fitness and cognitive functioning in older nursing home residents: a pilot study - Marmeleira, José (2018)
The main purpose of this pilot study was to examine the feasibility and the effects of a multimodal exercise intervention on the physical and cognitive functioning of institutionalized older people. Twentyone older adults (83.5 ± 4.9 years) living in two nursing home residences, were tested on two occasions 4 weeks apart to establish a baseline measure, and then engage in the exercise program twice weekly for 8 weeks. Participants were tested again after the exercise program. Almost all physical fitness and cognitive tests were unchanged at baseline measures, but after the exercise program, significant improvements(p < 0.05) were found in all physical fitness variables (strength, cardiorespiratory endurance,flexibility and balance) and in the majority of cognitive variables(visual attention, executive functioning and information processing speed). Exercise merging physical and cognitive stimulation could have broad impacts in the individual’s level of functioning and should be promoted in nursing home residences for the elderly.